Effects of perceptual similarity but not semantic association on false recognition in aging - Burnside, Kayleigh; Hope, Caroline; Gill, Emma; Morcom, Alexa M. (PeerJ, 2017)
This study investigated semantic and perceptual influences on false recognition in older and young adults in a variant on the Deese-Roediger-McDermott paradigm. In two experiments, participants encoded intermixed sets of semantically associated words, and sets of unrelated words. Each set was presented in a shared distinctive font. Older adults were no more likely to falsely recognize semantically associated lure words compared to unrelated lures also presented in studied fonts. However, they showed an increase in false recognition of lures which were related to studied items only by a shared font. This increased false recognition was associated with recollective experience. The data show that older adults do not always rely more on prior knowledge in episodic memory tasks. They converge with other findings suggesting that older adults may also be more prone to perceptually-driven errors.
Keywords: Cognitive aging; Aging; Episodic memory; False memory; DRM; Recognition memory; Perceptual false memory; Semantic false memory; False recollection